'Frog people' of the Drakensberg - Thorp, C. (Southern African Humanities, 2013)
This research explores the significance of three rock shelters (Vaalekop Shelter, Willcox Shelter and Sorcerer’s Rock) to the people who frequented and painted them. Two of the shelters (Willcox Shelter and Sorcerer’s Rock) contain painted figures that have been variously interpreted as representations of mythical beings (Sorcerer’s Rock and Willcox Shelter), as a medicine man (Willcox Shelter), and as ‘mythic women’ , a category that includes paintings from elsewhere in southern Africa (Sorcerer’s Rock and Willcox Shelter). I argue that these two figures have frog-like characteristics. Frogs feature in three major aspects of Bushman belief and ritual practice: rain, girls’ puberty and hunting. I interpret the symbolism of the two painted figures using folklore and accounts of ritual practice. I conclude that they are best interpreted in terms of beliefs concerning girls’ puberty, as well as those surrounding rain and hunting. At the third shelter (Vaalekop), girls’ puberty beliefs may be represented by a painting of a female eland in a mating stance. These three ideological realms underpin the social order of the people who used the shelters.